2017
DOI: 10.26638/470.203x
|View full text |Cite
|
Sign up to set email alerts
|

A Contrastive Analysis Between British and American Varieties: A Case-Study of English Accents

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, the differences between British and American English in this study were concluded from the study of (Tibenská, 2012) entitled Comparative Analysis of British and American English, the study done by (Sulaiman & Yuliani, 2017) entitled A Contrastive Analysis between British and American Varieties: A Case-study of English Accents, and journal of (Fares, n.d.) entitled British English and American English: History and Differences. The differences are listed below as follow:…”
Section: British and American English Differencesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the differences between British and American English in this study were concluded from the study of (Tibenská, 2012) entitled Comparative Analysis of British and American English, the study done by (Sulaiman & Yuliani, 2017) entitled A Contrastive Analysis between British and American Varieties: A Case-study of English Accents, and journal of (Fares, n.d.) entitled British English and American English: History and Differences. The differences are listed below as follow:…”
Section: British and American English Differencesmentioning
confidence: 93%
“…Vol.7/Nomor 2/Oktober 2021 Thus, studies on the lexical differences between British and American English have been undertaken by many researchers worldwide using a multiplicity of perspectives and approaches. Those studies fall under three major areas based on the methods that they used, namely 1) survey method: (Lindell, 2014), Thörnstrand (2008), and (Halldórsdóttir, 2014), 2) contrastive method: (Sukmawati, 2017), (Sulaiman & Yuliani, 2017) 3) corpus method: (Wilkinson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The English language is a foreign language for Indonesia, and the second language for Indonesia is a local language that is different in every single area in Indonesia. According to Fromkin, Rodman, & Hyams (2013) (as cited in (Sulaiman & Yuliani, 2017)), language is identified as a means or instrument of communication used by people whenever they come together, whether they play, fight, make love, or make automobiles, and they talk. One of the languages that is used most in English.…”
Section: Introductionmentioning
confidence: 99%
“…(Richards, et al, 2002) in Sulaiman & Syahri, 2022;Sulaiman, Syahri & Saputri, 2022). It can also be defined as a set of arbitrary symbol having conventionalized meanings and being used for communication, operating in a speech community (Sulaiman, 2020;Sulaiman, 2018;Sulaiman, 2017;Sulaiman & Yuliani, 2017). Language refers to the concrete act of speaking, writing or signing in a given situation.…”
Section: Introductionmentioning
confidence: 99%